2013
DOI: 10.1242/bio.20134986
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the osteoblast precursor differentiation towards mature osteoblasts induced by continuous BMP-2 signaling

Abstract: SummaryMature osteoblasts are the cells responsible for bone formation and are derived from precursor osteoblasts. However, the mechanisms that control this differentiation are poorly understood. In fact, unlike the majority of organs in the body, which are composed of “soft” tissue from which cells can easily be isolated and studied, the “hard” mineralized tissue of bone has made it difficult to study the function of bone cells. Here, we established an in vitro model that mimics this differentiation under phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
1
33
0
1
Order By: Relevance
“…Besides, cytoskeleton reorganization affects osteoblastic differentiation (Yourek, Hussain, & Mao, ). The perturbation of the F‐actin cytoskeleton organization abolished the osteoblast differentiation process (Zouani, Rami, Lei, & Durrieu, ) and transient dynamic actin cytoskeletal reorganization stimulated osteoblastic differentiation (Higuchi, Nakamura, Yoshikawa, & Itoh, ). Wang et al, have shown that cytoskeleton reorganization is involved in lanthanum‐promoted both osteoblast proliferation and differentiation (Wang, Huang, Zhang, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cytoskeleton reorganization affects osteoblastic differentiation (Yourek, Hussain, & Mao, ). The perturbation of the F‐actin cytoskeleton organization abolished the osteoblast differentiation process (Zouani, Rami, Lei, & Durrieu, ) and transient dynamic actin cytoskeletal reorganization stimulated osteoblastic differentiation (Higuchi, Nakamura, Yoshikawa, & Itoh, ). Wang et al, have shown that cytoskeleton reorganization is involved in lanthanum‐promoted both osteoblast proliferation and differentiation (Wang, Huang, Zhang, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these, the microenvironment are also important for osteogenic differentiation [35,36]. BMPs belong to the TGF- b super-family and are considered to have critical roles not only in bone development [8,37] BMP9, also known as growth differentiation factor 2 (GDF2), has been reported as the most potential member of BMPs to promote osteogenic differentiation in MPCs [9], which can be used as an efficacious factor in tissue engineering together with suitable biomaterials for bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In the first example, we have developed a differentiation model and have characterized differentiated cells by using this superresolution wide-field optical profilometry microscopy technique. We have induced cell swelling and have demonstrated that the cell fixation method (which also involves gold or titanium deposition) does not alter the surface topography to any significant degree thus ruling out any artifacts [32], [44]. In a second example, we have developed another nanotopographical model for stem cell differentiation and have analyzed cell adhesion and collective cell organization by using the same superresolution technique.…”
Section: Methodsmentioning
confidence: 99%